Does Coaching Affect Employee Work Professionalism? A study of the state apparatus in Indonesia - Siti Syahsudarmi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
The purpose of this study was to determine the effect of coaching on the professionalism of government employees in Riau Province, Indonesia. This research is a quantitative study using SPSS Version 23 to process data and test hypotheses. It was found that coaching had a significant effect on the professionalism of employees' work. It is known that coaching has an effect of 78.2% on the Professionalism of Government Employees while the remaining 21.8% is influenced by other variables outside of this study.